Phenolic glycosides from Antidesma ghaesembilla - Viet Cuong, Le Canh; Trang, Do Thi; Nhiem, Nguyen Xuan; Yen, Pham Hai; Tai, Bui Huu; Tuan Anh, Hoang Le; Huong, Le Mai; Binh, Nguyen Quoc; Minh, Chau Van; Kiem, Phan Van (Vietnam Journal of Chemistry, 2016)
Five phenolic glycosides, vanillyl alcohol 4-O-β-D-glucopyranoside, 4-hydroxy-3,5-dimethoxybenzyl-O-β-D-glucopyranoside, 3-hydroxy-4,5-dimethoxyphenyl-O-β-D-glucopyranoside, 3,4,5-trimethoxyphenyl-O-β-D-glucopyranoside, and sinapyl alcohol 4-O-β-D-glucopyranoside (1-5), respectively were isolated from the methanol extract of the Antidesma ghaesembilla leaves. Their structures were elucidated by spectroscopic methods and in comparison with the published data. Compounds 1-3 were reported from Euphorbiaceae family for the first time, compounds 4 and 5 were reported from Antidesma genus for the first time. Keywords. Antidesma ghaesembilla, Euphorbiaceae, phenolic.